The Influence Of Job Stress And Job Satisfaction On Employee Performance Through Organizational Commitment As An Intervening Variable Among Non-Civil Servant Staff At UIN Raden Fatah Palembang - Dwi Rahmadanti; Zunaidah, Zunaidah; Marlina Widiyanti; Yos Kamarudin; Muhammad Ichsan Hadjri (SEAN Institute, 2024)
The aim of this study is to obtain empirical evidence on the influence of job stress and job satisfaction on the performance of non-civil servant administrative staff at UIN Raden Fatah Palembang, with organizational commitment as an intervening variable. This research employs descriptive statistics with quantitative data and SEM (Structural Equation Model) using the Smart PLS application, with a sample size of 160 people. The results of this study indicate that job stress and job satisfaction significantly affect employee performance, job stress and job satisfaction significantly affect organizational commitment, organizational commitment significantly affects performance, job stress affects performance with organizational commitment as an intervening variable, but job satisfaction does not affect performance with organizational commitment as an intervening variable. This study recommends that the management of UIN Raden Fatah employees should enhance effective job satisfaction and consider other factors that can influence employee performance.